Leadership, Organizational Culture, Organizational Justice on Organizational Commitments and Employee Performance Contract in Private Hospitals - Dwi Cahyadi Putra Aditya (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACTThe purpose of this study was to analyze the variables of Leadership, Organizational Culture, Organizational Justice Against Organizational Commitment and Contract Employee Performance at Private Hospitals. This researcher was conducted at the Premagana Hospital in Gianyar. Data collection techniques using questionnaires and interviews with a sample of 150 respondents. This research technique with Amos for Windows 23.0 analysis process, starts from the evaluation process of SEM assumptions through evaluation of data normality, Confirmatory factor analysis (CFA) and influence analysis with SEM. The results of this study indicate that the CR value of 2.704> 2,000 and Probability = 0.007 <0.05 indicates that the effect of leadership variables on organizational commitment is a significant positive effect CR value 3.459> 2,000 and Probability = *** <0.05 indicates that influence the organizational culture variable on organizational commitment is a significant positive effect. CR value 4.181> 2,000 and Probability = *** <0.05 indicates that the influence of organizational justice variables on organizational commitment is a significant positive effect. The value of CR 2.165> 2,000 and Probability = 0.030 <0.05 indicates that the influence of leadership variables on employee performance is a significant positive effect. CR value 4.527> 2,000 and Probability = *** <0.05 indicates that the influence of organizational culture variables on employee performance is a significant positive effect. The CR value of 0,233 <2,000 and Probability = 0,823 <0,05 shows that the influence of organizational justice variables on employee performance is a positive and insignificant effect. CR value of 2.193> 2,000 and Probability = 0.002 <0.05 indicates that the influence of organizational commitment variables on employee performance is a significant positive effect.